2021
DOI: 10.1097/jpa.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Admissions and Underrepresented Minorities in Physician Assistant Programs

Abstract: Purpose The purpose of this study was to assess holistic review use in physician assistant (PA) programs and determine whether a relationship between holistic review and underrepresented minority (URM) matriculation exists. Methods Using data from the 2016–2017 Physician Assistant Education Association annual survey of PA programs, we examined the frequency of holistic review use across PA programs. Bivariate correlation analyses and binary logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The Physician Assistant (PA) profession has undergone phenomenal growth in the past 50 years; nonetheless areas of diversity, inclusion, and health care equity remain a challenge [1][2][3]. The percentage of minority PAs remains disproportionately small despite many efforts to increase workforce diversity over the past several decades [4][5][6][7]. The National Commission on Certification of Physician Assistants (NCCPA) reported that over 80% of practicing PAs were white from 2016-2020 [8].…”
Section: Introductionmentioning
confidence: 99%
“…The Physician Assistant (PA) profession has undergone phenomenal growth in the past 50 years; nonetheless areas of diversity, inclusion, and health care equity remain a challenge [1][2][3]. The percentage of minority PAs remains disproportionately small despite many efforts to increase workforce diversity over the past several decades [4][5][6][7]. The National Commission on Certification of Physician Assistants (NCCPA) reported that over 80% of practicing PAs were white from 2016-2020 [8].…”
Section: Introductionmentioning
confidence: 99%
“…23 Holistic admissions, as defined by the AAMC, "considers each applicant individually by balancing their academic metrics with experiences and attributes. 34 Coplan et al 35 reported that a large majority of PA programs use elements of holistic review in their admissions process, but use of holistic admissions was inconsistent in increasing URM student enrollment. Programs that used holistic review had, on average, a slight increase in average first-year URM matriculation compared with those that did not use holistic Defined Elements of Holistic Review 35 1) Broad-based selection criteria that are clearly linked to school mission and goals that promote diversity as a vital element for achieving excellence 2) Balanced consideration of applicants' experiences, attributes, and academic metrics 3) Individualized consideration of how each applicant might contribute to the learning environment and to the profession 4) Consideration of race and ethnicity (where legal) when such consideration is narrowly tailored to achieve mission-related educational goals…”
Section: Holistic Admissionsmentioning
confidence: 99%
“…23 Holistic admissions, as defined by the AAMC, “considers each applicant individually by balancing their academic metrics with experiences and attributes. 34 Coplan et al 35 reported that a large majority of PA programs use elements of holistic review in their admissions process, but use of holistic admissions was inconsistent in increasing URM student enrollment. Programs that used holistic review had, on average, a slight increase in average first-year URM matriculation compared with those that did not use holistic admissions.…”
Section: Matriculationmentioning
confidence: 99%
“…Several studies have demonstrated a direct relationship between the implementation of a holistic review process and an increase in the number of BIPOC and overall diversity among admitted students in their respective healthcare programs. [17][18][19][20] Historically, PA programs have struggled with recruiting and admitting BIPOC individuals. 21 Utilizing the program mission or charge, vision, and goals is necessary to proceed with the development of a holistic-driven admissions process that will ultimately lead to a paradigm shift in the diversity of the PA profession.…”
Section: Leadership Structurementioning
confidence: 99%